4(y + 2)(y + 2)
4y2 + 16y + 16 = 4(y2 + 4y + 4) = 4(y2 + 2y + 2y + 2) = 4[y(y + 2) + 2(y + 2)] = 4(y + 2)2
It is: 2(4x+5)
4y2+16y+16=0 Divide by 4 on both sides: y2+4y+4=0 Factorise: (y+2)(y+2)=0 Therefore y= -2
To simplify the expression 8xy over 16y, we first cancel out common factors in the numerator and the denominator. Both 8 and 16 can be divided by 8 to get 1 and 2, respectively. The y in the numerator cancels out with one of the y's in the denominator. This leaves us with x over 2 as the simplest form of the expression.
x^2 plus 16y?
4(y + 2)(y + 2)
4(y + 2)(y + 2)
4y2 + 16y + 16 = 4(y2 + 4y + 4) = 4(y2 + 2y + 2y + 2) = 4[y(y + 2) + 2(y + 2)] = 4(y + 2)2
4(3y + 2)(7y - 6)
3(2 + y)
It is: 2(4x+5)
4y2+16y+16=0 Divide by 4 on both sides: y2+4y+4=0 Factorise: (y+2)(y+2)=0 Therefore y= -2
2(x+3)
(y + 8)(y - 2)
y + y + 2 = 182y + 2 = 182y = 16y = 8whew !
(y + 8)(y - 2)